Examination of the Weinberger Adjustment Inventory—Short Form Among Portuguese Young Adults: Psychometrics and Measurement Invariance - Pechorro, Pedro (International journal of offender therapy and comparative criminology, 2023)
The Weinberger Adjustment Inventory—Short Form (WAI-SF) is a multidimensional measure of behavioral adjustment frequently used with forensic, clinical, and community populations. However, no previous studies have examined the WAI-SF from a more modern psychometric perspective including second-order models, measurement invariance and a better estimation of reliability. The current sample is composed of female and male young adults (N = 610, M = 21.33 years, SD = 3.09, range = 18–37) from a university context in Portugal. Results indicated that both the four-factor intercorrelated and the four-factor second order models of the WAI-SF Distress and Restraint scales showed good fits. The WAI-SF Distress and Restraint scales were negatively and significantly correlated, and the intercorrelations between the subscales of each scale ranged from moderate to high. The WAI-SF scales and subscales mostly showed adequate to good reliability in terms of McDonald’s Omega and the more traditional Cronbach’s Alpha. Strong cross-gender measurement invariance was demonstrated, with females scoring significantly higher than males on the Anxiety subscale of the Distress scale, and on the Suppression of Aggression, Impulse Control, Consideration of Others, Responsibility subscales, and Restraint scale. The WAI-SF scales and subscales showed distinctive correlates with other measures (e.g., low self-control, psychopathy) and variables (e.g., delinquency seriousness, substance use). Considering our findings, the use of the WAI-SF is recommended among the Portuguese young adult population and its use in criminological research is encouraged.